2006
DOI: 10.1016/j.ceb.2006.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum architecture: structures in flux

Abstract: The endoplasmic reticulum (ER) is a dynamic pleiomorphic organelle containing continuous but distinct subdomains. The diversity of ER structures parallels its many functions, including secretory protein biogenesis, lipid synthesis, drug metabolism and Ca 2+ signaling. Recent studies are revealing how elaborate ER structures arise in response to subtle changes in protein levels, dynamics, and interactions as well as in response to alterations in cytosolic ion concentrations. Subdomain formation appears to be go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
150
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(160 citation statements)
references
References 60 publications
4
150
1
5
Order By: Relevance
“…When GFP-b(5)tail is acutely overexpressed, it causes architectural rearrangements of the ER that are easily discernible by fluorescence microscopy (14). In agreement with its modest concentration, however, the construct did not alter ER architecture in the HeLa-TetOff cell line (15) (Fig.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…When GFP-b(5)tail is acutely overexpressed, it causes architectural rearrangements of the ER that are easily discernible by fluorescence microscopy (14). In agreement with its modest concentration, however, the construct did not alter ER architecture in the HeLa-TetOff cell line (15) (Fig.…”
Section: Resultsmentioning
confidence: 49%
“…The latter response, known as the ER overload response, depends both on Ca 2+ leakage from the ER lumen and on reactive oxygen species (ROS) and may represent a cellular defense mechanism rather than a signaling pathway causally linked to membrane proliferation. High loads of transfected ER resident membrane proteins also often cause striking architectural rearrangements of the organelle (14), but how these relate to the modulation of ER size in response to altered levels of endogenous membrane proteins is not clear.…”
mentioning
confidence: 99%
“…Each subdomain contains a unique set of proteins that are responsible for its function and organization. ER subdomains are relatively stable, but they can be transformed into alternative structures in response to cellular conditions (for review, see Voeltz et al, 2002;Levine and Rabouille, 2005;Borgese et al, 2006;Vedrenne and Hauri, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Each subdomain contains a unique set of proteins that are responsible for its function and organization. ER subdomains are relatively stable, but they can be transformed into alternative structures in response to cellular conditions (for review, see Voeltz et al, 2002;Levine and Rabouille, 2005;Borgese et al, 2006;Vedrenne and Hauri, 2006).Several studies showed the presence of a specialized ER subdomain that is related to ER-associated degradation (ERAD). ERAD is part of a quality control system that ensures the delivery of only correctly folded or assembled secretory and membrane proteins to their final destinations.…”
mentioning
confidence: 99%
“…T he endoplasmic reticulum (ER) is a large interconnected membrane network that plays a major role in lipid biosynthesis in eukaryotic cells (Borgese et al 2006). Newly synthesized lipids at the ER are then delivered to different cellular membranes or organelles, each of which shows unique lipid and protein composition and executes distinct cellular function (Holthuis et al 2003).…”
mentioning
confidence: 99%